A CONTRADICTORY RELATIONS AND PERPETUATION OF COLONIAL DISCOURSE IN INDONESIA DARI PINGGIR BY FATRIS MF - Luhfi, Muhammad; Anggi Puspitasari (IAIN Surakarta, 2025)
This research aims to describe the travel novel Indonesia dari Pinggir by Fatris MF that tries to convey to the world the charm of people, culture, and regions in the Eastern part of Indonesia. However, at the same time, the author presents contradictory narratives, irony, negotiation, and efforts to accommodate the voice of the East to be in dialogue and even contrasted with the West. Therefore, the researcher conducted an academic exploration of the author's ambivalent position, simultaneously resisting and perpetuating the colonial discourse. This research is descriptive qualitative research. The data in this research were taken from the novel Indonesia dari Pinggir by Fatris MF, consisting of words, phrases, sentences, paragraphs, and dialog between characters related to the research problem. Using Carl Thompson's concept of travel writing, the researcher found that the strategies of reporting the world and representing the other in this novel reveal the eastern Indonesian people who are often described as